Jump off the beam: functional and anthropometrical characteristics of elite Belgian women`s artistic gymnasts - Dhoe, B.; Boone, J.; Colosio, A. L. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Elite Womens Artistic Gymnastics is a complex sport that requires high physiological and technical demands from childhood onwards. Knowledge of the functional and anthropometrical characteristics of high level gymnasts is paramount to guide selection, training and recovery strategies throughout the growth and development (1; 2). While some information about gymnasts physiques is available, there is limited knowledge about gymnasts` functional characteristics, and a need for country-specific databases (3). Therefore, this investigation was aimed at providing up-to-date functional and anthropometrical data of elite Belgian women`s artistic gymnasts. METHODS: Between November 2021 and January 2024, we screened 19 female artistic gymnasts belonging to the Belgian national team to assess anthropometrical characteristics (i.e., height, body weight (BW), body fat%, and bone density Z-score), maximal strength (i.e., 1 rep-max (1RM) for squat, half squat, leg press, bench press, and bench pull), cardiovascular fitness (i.e., VO2max, ventilatory thresholds 1 and 2 for running), jump height and flexibility. For analysis, the most recent and complete representative values were used. Average values and standard deviation were assessed per variable. RESULTS: Mean age at the time of screening was 17.8 ± 2.3 years, with 2 individuals categorized as junior and 17 as senior. The mean height upon screening was 158.8±6.4cm, BW was 52.1±7,6kg, bodyfat% was 20.8±4.3% and bone density Z-score was 1.2±1.1. As for mean strength values, relative 1RM to BW for squat was 1.3±0.2kg×BW-1, 2.6±0.5kg×BW-1 for half squat, 4.9±0.9kg×BW-1 for leg press, 0.9±0.1kg×BW-1 for bench press and 1.0±0.1kg×BW-1 for bench pull. Concerning mean cardiovascular fitness, VO2max was 51.3±3.4ml/min/kg, the mean ventilatory threshold 1 and 2 occurred at 68.8±4.4% and 85.1±3.6% of VO2max respectively. Regarding jumping performance, squat jump was 26.0±3.7cm, counter movement jump was 27.6±3.2cm, counter movement jump with arms was 34.9±3.6cm, single leg jump for the right leg was 15.0±2.6 and 14.9±2.7cm for the left leg. It was found that flexibility was considerably higher compared to a non-gymnast reference population, except for wrist supination which was lower (4; 5). CONCLUSION: Our sample of elite Belgian women`s artistic gymnasts have similar height, BW, VO2max and relative 1RM to BW for squat compared to values observed in other countries (6; 7). Bodyfat% is within the range but at the higher end than earlier examined (3), while jump heights were lower (6). Bone density and flexibility were higher than the non-gymnast reference population, with the exception of wrist supination which was lower (8). Finally, there is a need to integrate upper body strength measures in elite female gymnasts to allow for quantitative comparisons.